Diverse autophagy and apoptosis in myeloid leukemia cells induced by 20(s)-GRh2 and blue LED irradiation. Issue 67 (28th November 2019) - Zhuang, Jianjian; Yin, Juxin; Xu, Chaojian; Jiang, Mengmeng; Lv, Shaowu
Abstract : Blue LED and 20(S)-GRh2 induced apoptosis and autophagy in cells. Abstract : Autophagy is an important mechanism for cell death regulation. To improve the anticancer effect during the treatment of leukemia and promote the apoptosis of leukemic cells, it is important to define the relationship between autophagy and apoptosis. A key bioactive compound in traditional Chinese medicine, 20(s)-Ginsenoside (GRh2), demonstrated an advancement in leukemia treatment. Blue LED therapy (BL) is a physical treatment method that can induce leukemic cell death. In this study, we tested the effect of 20(s)-GRh2, BL, and their combination (BL–GRh2) on the activation of leukemic cell apoptosis and autophagy. Both treatments, whether used individually or simultaneously, induce apoptosis through the induction of reactive oxygen species (ROS), disrupted mitochondrial membrane potential (MMP) and regulated the expression of apoptosis-related genes and proteins. Furthermore, using western blotting to analyze the autophagy markers LC3B and P62, we detected the activation of autophagy. In cells treated with autophagy inhibitor 3-MA, both autophagy and apoptosis were inhibited, either by BL alone or by BL–GRh2. However, apoptosis in 20(s)-GRh2-treated cells was enhanced. In cells treated with apoptosis suppressor Z-VAD-FMK, autophagy was inhibited in the BL and BL–GRh2-treated cells, although it was enhanced in cells treated with 20(s)-GRh2 alone. Moreover, we observed a stronger induction of apoptosis by BL–GRh2 in myeloid leukemia cells. Our data indicate that autophagy induced by different factors can play diverse roles on the same cells. Our results also indicate that the combination of traditional Chinese medicine with physical therapy may be a new strategy for anti-cancer therapy.